Determination of Water Pollution Levels Sibam River Pekanbaru Based Biotic Index Macrozoobenthos - Irwandi Manalu; Nur El Fajri; Adriman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The study aims to determine the level of River Water Pollution Sibammacrozoobenthos Pekanbaru based biotic index that has been carried out inDecember 2013 - January 2014 . Taking samples taken at 4 stations ( upstream,midstream, downstream ). Each station consists of 3 locations ( plots ) with arepetition time interval for one week .Macrozoobenthos organisms found in the waters of the River SibamPekanbaru during the study was divided into a number of Class / Order / FamilyViviparidae, Naididae, Lymnaeidae, Tubificidae, Bithyniidae, and orderDecapoda.Results average Family Biotic Index ( FBI ) During the study ranged from6,25-7,05. Family Biotic Index values highest in Station I is 7,05 and the lowest atStation IV is 6,25. From this result, the waters of the River sibam on WaterQuality Station I with rather poor and heavily polluted pollution level of organicmatter. At Station II and III are 6,42 and 6,53 with the quality and level ofcontamination of waters polluted by very much. At Station IV with water quality abit worse with the level of pollution Contaminated much.Results average measurement physicochemical parameters foundTemperatures is 27,8–29,22 0C, Turbidity is 18,44–44,56 NTU, Flow Speed is0,19–0,42 m/s, TSS is 6,22-23 mg/l , Depth is 0,33–1,94 m , pH is 5 , DissolvedOxygen is 5,68– 7,95 mg/l, COD is 18,93–28,91 mg/l, BOD5 is 2,98–4,18 mg/l,Organic Materials is 13,06–29,3 % .Key words : Macrozoobenthos, Biotic Index, Family Biotic Index (FBI), WaterQuality, River Sibam Pekanbaru.